Direct Interaction of Ca(V)β with Actin Up-regulates L-type Calcium Currents in HL-1 Cardiomyocytes - Stölting, Gabriel (J Biol Chem, 2015)
Expression of the β-subunit (Ca(V)β) is required for normal function of cardiac L-type calcium channels, and its up-regulation is associated with heart failure. Ca(V)β binds to the α(1) pore-forming subunit of L-type channels and augments calcium current density by facilitating channel opening and increasing the number of channels in the plasma membrane, by a poorly understood mechanism. Actin, a key component of the intracellular trafficking machinery, interacts with Src homology 3 domains in different proteins. Although Ca(V)β encompasses a highly conserved Src homology 3 domain, association with actin has not yet been explored. Here, using co-sedimentation assays and FRET experiments, we uncover a direct interaction between Ca(V)β and actin filaments. Consistently, single-molecule localization analysis reveals streaklike structures composed by Ca(V)β(2) that distribute over several micrometers along actin filaments in HL-1 cardiomyocytes. Overexpression of Ca(V)β(2)-N3 in HL-1 cells induces an increase in L-type current without altering voltage-dependent activation, thus reflecting an increased number of channels in the plasma membrane. Ca(V)β mediated L-type up-regulation, and Ca(V)β-actin association is prevented by disruption of the actin cytoskeleton with cytochalasin D. Our study reveals for the first time an interacting partner of Ca(V)β that is directly involved in vesicular trafficking. We propose a model in which Ca(V)β promotes anterograde trafficking of the L-type channels by anchoring them to actin filaments in their itinerary to the plasma membrane.